Wybrane aspekty metodyki badań holistycznej edukacji środowiskowej w świetle idei zrównoważonego rozwoju - Jan Sandner (Studia Ecologiae et Bioethicae)
The concept of the balanced development idea caused a renewed view on the problems in the area of the research methodology in environmental education. The aforesaid viewis related to the necessity of implementing methods in which an appropriate place will be found for a holistic approach to occurring environmental processes. An approach enabling interdisciplinarity of this problem will finally find its solution also in a new teaching method. This forces a new quality of a perceptive view of the environment, however by no means severing from the accepted research methodology enforced in nature sciences.